The Proposal of Integrated Actions in Transport as Part of a Climate Action Plan for UNICAMP - Melo, Mayara; Cavaliero, Carla; Moraes, Bruna; Dalbelo, Thalita (Universitas Diponegoro, 2024)
Since 2019, the State University of Campinas (UNICAMP) has been collecting data, preparing, and annually monitoring sustainability indicators submitted to the UI GreenMetric ranking, which guide improvement projects at the university in alignment with the Sustainable Development Goals (SDGs). This article aims to propose sustainable practices for managing urban mobility on its campuses, drawing inspiration from the experiences of national and international universities that ranked highest in the 2023 edition of the aforementioned ranking. The study employed both qualitative and quantitative research methods, using a descriptive approach combined with Deductive Content Analysis (DCA). This analysis was further validated by the Multi-Criteria Decision-Making (MCDM) method known as Fuzzy SWARA. Through this process, the study identified the most commonly adopted actions by universities: promoting the use of electric and/or conventional bicycles on campus (11.8%); projects in partnership with government, state, or municipal entities to develop express cycle paths and encourage bicycle use both on campus and in the city (9.2%); conventional bicycle rental on campus (9.2%); and electric car sharing on campus (9.2%). The proposals suggested for UNICAMP include encouraging carpooling, implementing a public transportation exemption or half-fare program for employees, promoting the use of bicycles while ensuring increased campus security, among other initiatives. This research is part of a proposal for a Climate Action Plan for the university, which aims to effectively integrate sustainability into the university's agenda and support the fight against the climate emergency through necessary adaptations.